2006
DOI: 10.1093/nar/gkj139
|View full text |Cite
|
Sign up to set email alerts
|

The LIFEdb database in 2006

Abstract: LIFEdb () integrates data from large-scale functional genomics assays and manual cDNA annotation with bioinformatics gene expression and protein analysis. New features of LIFEdb include (i) an updated user interface with enhanced query capabilities, (ii) a configurable output table and the option to download search results in XML, (iii) the integration of data from cell-based screening assays addressing the influence of protein-overexpression on cell proliferation and (iv) the display of the relative expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…Tagging of endogenous proteins, which has been applied successfully to the yeast proteome ( 46, 57 ), has been extended to mouse but is not yet a high-throughput method ( 82 ). Large-scale efforts to visualize tagged exogenous proteins in mammals include the ongoing lifeDB project (http://www.lifedb.de) ( 66 ) and the completed MitoCarta project (http://www.broadinstitute.org/pubs/MitoCarta) ( 83 ). Currently, there are a total of 321 human proteins and 166 mouse mitochondrial proteins evidenced through microscopy, according to the MitoMiner database ( 97 ).…”
Section: Defining the Mitochondrial Proteomementioning
confidence: 99%
“…Tagging of endogenous proteins, which has been applied successfully to the yeast proteome ( 46, 57 ), has been extended to mouse but is not yet a high-throughput method ( 82 ). Large-scale efforts to visualize tagged exogenous proteins in mammals include the ongoing lifeDB project (http://www.lifedb.de) ( 66 ) and the completed MitoCarta project (http://www.broadinstitute.org/pubs/MitoCarta) ( 83 ). Currently, there are a total of 321 human proteins and 166 mouse mitochondrial proteins evidenced through microscopy, according to the MitoMiner database ( 97 ).…”
Section: Defining the Mitochondrial Proteomementioning
confidence: 99%
“…So far systematic studies of subcellular localization of proteins have been performed either with cellular fractionation (2) or fluorescence microscopy (3,4). The most commonly used approach in the latter case is based on transfection of cells with cDNA clones fused to a fluorescent reporter protein, like green fluorescent protein.…”
Section: Molecular and Cellular Proteomics 7:499 -508 2008mentioning
confidence: 99%
“…Although numerous experiments have shown the usefulness of this approach (3,4), recent studies have indicated that green fluorescent protein can induce translocation to the nucleus causing artifactual localization results (5).…”
Section: Molecular and Cellular Proteomics 7:499 -508 2008mentioning
confidence: 99%
“…Vacuole membrane protein 1 has been predicted to be a seven transmembrane protein (Hirokawa et al, 1998;Figure 2a) and the overexpressed human protein was reported to localize to the ER and Golgi apparatus (Starkuviene et al, 2004;Mehrle et al, 2006). The overexpressed rat protein was shown to induce intracellular vacuole formation with Vmp1 integrated into the membrane of these vacuoles (Dusetti et al, 2002).…”
mentioning
confidence: 99%